Fundação Crê: além da compensação ambiental - um estudo de caso - Magalhães, Ana Amélia de Sousa (2007)
The objective of this paper is to analyze Fundação Crê, that was organized to attend to a Behavior Adjustment Agreement (TAC) signed in conjunction by the State of Bahia District Attorney, the company Rio Doce Manganês and the City of Simões Filho, based on the respective Responsible Social Enterprise project (SER). This paper tries to verify if the SER project was able to reach results beyond the aimed environmental compensation. This research also analyses the Third Sector, its origins and present development, linking it to the Environmental Question as well as discussing the sustainable development model. By using primary and secondary sources, the research indicated that the results obtained by project SER extrapolated those set by TAC, while being insufficient both in what concerns environmental recuperation and the creation of an environmentally awareness in the community.